Copolymeric Hydrogels with High Capacities of Hydration and Methylene Blue Adsorption in Water - Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier Ltd, 2024)
Copolymers based on monomethyl hydrogen itaconate (βHI) with 2-hydroxyethyl methacrylate (HEMA) and βHI with 2-hydroxypropyl methacrylate (HPMA) were prepared in different monomer molar ratios. The reactivity parameters of copolymerization (r1 and r2) were determined. The values obtained for r1 and r2 indicate that P(βHI-co-HEMA) exhibits a high tendency towards alternate copolymerization. Structural characterization of the copolymeric hydrogels was carried out using Fourier transform infrared (FTIR) and 1H NMR spectroscopies, where the characteristic signals of the constituent functional groups were observed. The typical thermal stability of the polymeric systems was observed by thermogravimetric analysis (TGA). In addition, the swelling capacity in water was evaluated, and a swelling percentage over 655 % and 1249 % presented P(βHI-co-HEMA) and P(βHI-co-HPMA) respectively, in a period of 15 days at pH 10, and presence of 0.05 M NaNO3. Additionally, methylene blue (MB) adsorption capacity was studied in batch mode by varying different experimental parameters. MB adsorption capacity of 122.79 mg g−1 and 112.24 mg g−1 were achieved for P(βHI-co-HEMA) and P(βHI-co-HPMA), respectively. The data obtained were fitted to the Elovich kinetic model and to a Redlich-Peterson isotherm. The thermodynamic parameters indicated that the adsorption phenomenon is spontaneous, endothermic and with a high probability of occurrence. The adsorption efficiency decreases by approximately 60 % in the presence of interfering ions (Na+, K+, Ca2+ and Cl−). The adsorbents are reusable and achieve high MB adsorption efficiency (90 % and 80 % for P(βHI-co-HEMA) and P(βHI-co-HPMA) respectively) in a textile-simulated wastewater. Based on the results obtained, it is concluded that P(βHI-co-HEMA) and P(βHI-co-HPMA) show great potential for use in adsorption of water molecules, for MB retention and purification of simulated effluents from the textile industry. © 2024 Elsevier Ltd